Impacts of land cover and land use change on long-term trend of land surface phenology: a case study in agricultural ecosystems - Xiaoyang Zhang; Lingling Liu; Geoffrey M Henebry (Environmental Research Letters, 2019)
Vegetation phenological trends during last few decades have been frequently reported and these trends are commonly assumed to result from climate change. With the widespread influence of both human activities and natural processes, however, land cover and land use change (LCLUC) has dominated across various ecosystems in more than one-third of world’s land surface. LCLUC could lead to changes in vegetation types and species composition at local to regional scales. Thus, we hypothesize that LCLUC can significantly influence phenological trends at an ecosystem scale. Here we tested this hypothesis in agricultural ecosystems composed of various crop types spanning the Midwest of the United States by analyzing satellite-observed land surface phenology from 1982 to 2014. Greenup onset dates in croplands occurred later at rates ranging from 0.18 to 0.67 d yr ^−1 at the state scale. This trend was due to significant areal increases in corn (maize) and soybean that have later emergence coupled with areal decreases in wheat and oats that have earlier emergence, despite a trend of warmer spring temperatures that aid earlier crop emergence. Overall, considering the long-term directional change in greenup onset dates across these croplands, two-thirds was attributable to LCLUC and one-third to climatic variation. This finding indicates that extensive LCLUC can be the primary driver of satellite-observed phenological trends, especially in intensively managed agricultural landscapes.